Fitness- and Healthcenter evaluation by resigned members - Georgios Zarotis (Exercise and Quality of Life)
The aim of the study is to examine if and to what extent the evaluations of fitness studios by persons who have recently resigned from their membership are related to general studio conditions such as studio atmosphere, facilities, trainer’s competence and other features. In other words, the question is whether there are typical prioritizations on positive or negative evaluations by dropouts from fitness sport. In the survey a total of 225 people, who had quitted their membership in the past, were questioned in a telephone inquiry. The study was conducted in a health-oriented fitness center in a major city in Germany. At the time of the study the fitness facility had up to 1.151 memberships. Among them, 59% of the members were women and 41% were men. The average age of the respondents was 43.5 years. The average duration of membership added up to 4.4 years. Overall, the various aspects of the studio offer and its surroundings were mostly rated as “good”.  The respondents appreciated particularly the coaches (friendliness, helpfulness, competence), followed by opening hours, trial training and the first impression.  The membership costs and individual aspects such as space, music and ventilation are assessed more critically, if not really badly. The data show that the various evaluation aspects were clearly assessed differently by the respondents, and that there was apparently little generalized information on the studio evaluation.